PEMBERESAN UTANG PAJAK PT UNITED COAL INDONESIA KEPAILITAN PUTUSAN NOMOR 557 K/PDT.SUS-PAILIT/2018 - Shodiq Aminullah; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2021)
In practice, the management and settlement of bankrupt assets often encounter disputes. This happened in the bankruptcy case of PT United Coal Indonesia, which had a tax debt that acted as a preferred creditor whose position was under a separatist creditor and the curator had not paid the debt until it was fully paid. Therefore, the main problem in this research is what is the position of the tax debt submitted by the creditor (Director General of Taxes) in bankruptcy and how to settle the tax debt in Decision Number 557 K/PdtSusBankrupt/2018 against PT UCI. The research method used is a descriptive normative research method based on secondary data, which is analyzed qualitatively by deductively drawing conclusions. The results of the study illustrate that the state in this case the tax debt should have a higher position than separatist creditors and concurrent creditors, and should prioritize its payments over other creditors as stipulated in Article 21 paragraph (3a) juncto paragraph 3 juncto paragraph 1 of Law Number 16 Year 2009 concerning General Provisions and Tax Procedures, and the curator should pay the tax debt until it is paid off.